2019
DOI: 10.1016/j.jmapro.2019.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Performance of nanolubricants containing MoS2 nanotubes during form tapping of zinc-coated automotive components

Abstract: The paper presents the first use of nanolubricants containing MoS 2 nanotubes for form tapping of zinc-coated steel. MoS 2 nanotubes are known for their superb low frictional, anti-wear and extreme pressure properties and have shown a promising performance as nanolubricant additive in many machining and forming applications. However their interfacial interaction with zinc-coated components commonly used in automotive applications and their synergisms and antagonisms with currently used additives in forming oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The structure of liquid hydrocarbon is rearranged in the external solvation shell of the nanotube leading to ordered layers following the nanotube symmetry and extending well beyond those molecules in close contact with the surface which precludes building of an efficient extended tribolayer in dynamic conditions. This liquid hydrocarbon restructuring around the nanotube and the strong interaction between both systems can be considered as the building up of an effective antiwear coating, explaining antiwear MoS 2 properties [14,15,16]. In the case of confined molecules, they develop also patterns in the region around the nanotube centre as well as in the vicinity of the internal nanotube surface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The structure of liquid hydrocarbon is rearranged in the external solvation shell of the nanotube leading to ordered layers following the nanotube symmetry and extending well beyond those molecules in close contact with the surface which precludes building of an efficient extended tribolayer in dynamic conditions. This liquid hydrocarbon restructuring around the nanotube and the strong interaction between both systems can be considered as the building up of an effective antiwear coating, explaining antiwear MoS 2 properties [14,15,16]. In the case of confined molecules, they develop also patterns in the region around the nanotube centre as well as in the vicinity of the internal nanotube surface.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, TMDs -nanoparticles [7,8], considering compounds such as MoS 2 [9] or WS 2 [10] have been largely tested under several tribological conditions and environments. TMDs nanoparticles as base oils additives have been considered in different forms, including fullerene-like [11], 2D monolayers [12,13] as well as nanotubes [14] and quantum dots [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, molybdenum sulphide (MoS 2 ) nano additives attract considerable attention, due to their distinctive wear properties, as mentioned in some studies [61,173]. It is believed that the friction-reduction capability of MoS 2 returns to its weak van der Waals primary atomic bonding that eases the slipping of MoS 2 layers and hence, forming the protective tribofilm [61].…”
Section: Discussionmentioning
confidence: 99%
“…This interaction was important to understand to benefit the future development of nanofluid minimum quantity lubrication formulations. Results from the studies showed MoS2 interacted favourably with the Zn coating to form a tribological surface with superb frictional performance (114).…”
Section: Sizementioning
confidence: 99%